Single-port robotic-assisted wet colostomy after total pelvic exenteration: a feasibility video report - Ronsini, Carlo; Solazzo, Maria Cristina; Di Donna, Mariano Catello; Cucinella, Giuseppe; Scaffa, Cono; Chiantera, Vito (Frontiers in Oncology, 2026)
BackgroundTotal pelvic exenteration (TPE) is a radical procedure involving the en bloc removal of pelvic organs. Among reconstructive strategies, wet colostomy—a single conduit for both urinary and fecal diversion—offers advantages such as reduced operative time and lower risk of ureteral anastomotic complications.ObjectiveThe aim of this study was to describe a case of wet colostomy performed entirely using a single-port (SP) robotic-assisted approach, demonstrating the feasibility of this minimally invasive technique.MethodsA case report study was conducted at the Gynecologic Oncology Unit of the Istituto Nazionale Tumori “Fondazione Pascale” in Italy. A pelvic recurrence of endometrial cancer was treated using the Da Vinci SP® robotic system. The voice-commented video article details both the TPE and reconstructive procedures. Primary outcomes included technical description, operative time, hospital stay, and blood transfusions.ResultsIn January 2025, a 68-year-old woman with pelvic recurrence of endometrial carcinoma underwent robotic-assisted TPE with wet colostomy. The procedure lasted 320 min, with an estimated blood loss of 50 cc, requiring no transfusion. The patient was discharged on postoperative day 4 without complications within the first 30 days.ConclusionThis is the first reported case of TPE with robotic SP-assisted wet colostomy. The video illustrates the surgical strategy and highlights the feasibility of this innovative technique.SynopsisThis report describes the technique of single-port robotic-assisted wet colostomy following total pelvic exenteration for recurrent endometrial cancer, providing a step-by-step overview of the surgical approach.